Analysis of COPRAS and ORESTE in Determining Superior Website Pages of Universities in Medan City - Akbar Idaman; Tar Muhammad Raja Gunung (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to evaluate the quality of university web pages in Medan City using two decision-making methods, namely Complex Proportional Assessment (COPRAS) and Organization Rangement Et Syntest De Relatonnelles (ORESTE). University websites play a very important role in reflecting the identity, vision, and mission of the institution, as well as improving its reputation in today's digital era. However, not all universities in Medan have implemented optimal standards in managing their web pages. Therefore, the results of this study show that based on the COPRAS method, there are 3 top universities, namely Muhammadiyah University of North Sumatra (UMSU) ranked first with the highest score of 100.0000, followed by Quality University with a score of 93.7500 ranked second, and Harapan University Medan with a score of 91.4063 ranked third. Meanwhile, using the ORESTE method also ranked UMSU first with a score of 5.00, followed by Universitas Pembangunan Panca Budi in second place, and Santo Thomas Catholic University in third place with a score of 7.17. The similarity of the first rank between the two methods shows consistency in the recognition of the quality of the UMSU web page. However, differences were seen in the second and third rankings, where COPRAS ranked Universitas Quality and Universitas Harapan Medan, while ORESTE ranked Universitas Pembangunan Panca Budi and Universitas Katolik Santo Thomas. This difference reflects the different evaluation approaches of the two methods. The findings are expected to assist universities in Medan in developing more effective strategies for improving user experience and strengthening institutional reputation.